The Influence of Corporate Social Responsibility (CSR) on The Performance of MSME Innovations Under the Guidance of PT. Indocement. Tbk Cirebon during the Covid-19 Pandemic - Ahmad Ali; Icuk Rangga Bawono; Muzayyanah (Enrichment : Journal of Management, 2022)
The performance of innovation in MSMEs is part of economic growth, the existence of MSMEs can support the national economy even though there is a storm of economic crisis, especially during the Covid-19 pandemic. This study aims to find out the influence of Corporate Social Responsibility on the performance of MSME Innovation in PT. Indocement during the Covid-19 pandemic. The research was quantitative, using Primary and Skunder data in taking primary data using a questionnaire distributed to 30 respondents while secondary data from the Cirebon Regency SME Cooperative Office of Industry and Trade. Furthermore, the analysis technique uses simple regression and classical assumption tests using SPSS software. The results of the analysis obtained from this study show that CSR has a positive and significant effect on the innovative performance of MSMEs under the guidance of PT Indocement during the Covid-19 pandemic